Hollow particles, resin composition and molded body
Patent Information
- Application Number
- JP2021562678
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-04
- Filing Date
- 2020-12-02
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-12-02
AI Technical Summary
【0015】 上記の如き本開示によれば、空隙率が高く、潰れ難く、揮発性化合物の含有量が低減された中空粒子、当該中空粒子と樹脂とを含有する樹脂組成物、及び当該樹脂組成物の成形体を提供することができる。
Smart Images

Figure 0007635717000001 
Figure 0007635717000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to hollow particles, a resin composition, and a molded article. More specifically, the present disclosure relates to hollow particles that are difficult to crush and have a reduced content of volatile compounds, a resin composition containing the hollow particles and a resin, and a molded article of the resin composition. [Background technology]
[0002] Hollow particles (hollow resin particles) are particles that have a cavity inside them, and compared with solid particles whose insides are substantially filled with resin, they scatter light well and have low light transmittance. Therefore, they are widely used as organic pigments with excellent optical properties such as opacity and whiteness, or as hiding agents in water-based paints, paper coating compositions, and the like, and further used as additives for molded articles such as light reflectors, heat insulating materials, and sound insulating materials.
[0003] For example, Patent Document 1 describes hollow polymeric microparticles having a single-layer structure in which the shell is made of a polymer or copolymer of at least one crosslinkable monomer, or a copolymer of at least one crosslinkable monomer and at least one monofunctional monomer, as hollow polymeric microparticles used in paints, paper coating compositions, etc. The hollow polymeric microparticles described in Patent Document 1 are obtained by dispersing a mixture of a crosslinkable monomer, an initiator, and a poorly water-soluble solvent in an aqueous solution of a dispersion stabilizer and carrying out suspension polymerization, and do not contain a resin polymerized in advance. In addition, in the examples of Patent Document 1, hollow polymeric microparticles having a shell thickness of about 1 μm are obtained.
[0004] Patent Document 2 describes hollow resin particles that can be used as coating agents, additives for molded bodies, etc., in which the shell has a region made of a non-crosslinking polymer on the side in contact with the hollow, does not have pinholes with a diameter larger than 5 nm, and has an average particle size of 0.05 μm to 1 μm. The hollow resin particles described in Patent Document 2 are obtained by dispersing a mixed solution containing a monomer mixture consisting of a polyfunctional monomer and a monofunctional monomer, a non-reactive solvent, a polymerization initiator, and a non-crosslinking polymer in an aqueous solution, and then polymerizing the solution. In the examples of Patent Document 2, the ratio of the polyfunctional monomer to the total amount of the polyfunctional monomer and the monofunctional monomer is 50% by weight or 35% by weight. In the examples of Patent Document 2, hollow resin particles are obtained in which the average particle size is 0.19 μm to 0.36 μm and the ratio of the shell thickness to the average primary particle size is 0.13 to 0.21.
[0005] On the other hand, Patent Document 3 describes hollow resin particles that can be used as microcapsules, which have a thermal decomposition starting temperature of 350° C. or more, a shell having fine through-holes with a diameter in the range of 10 to 50 nm, and a thickness ratio of 0.03 to 0.25 with respect to the average primary particle diameter of the hollow resin particles. The hollow resin particles described in Patent Document 3 are obtained by dispersing a mixed solution containing a polyfunctional monomer, a non-reactive solvent, and a water-soluble polymerization initiator in an aqueous solution, and then polymerizing the mixture, and do not contain a resin that has been polymerized in advance. In the method of Patent Document 3, a water-soluble polymerization initiator such as potassium persulfate is used as the polymerization initiator, which makes it easy to generate fine through-holes in the shell. In addition, in the examples of Patent Document 3, hollow resin particles are obtained with an average particle diameter of 0.23 μm to 0.45 μm and a shell thickness ratio of 0.06 to 0.17 with respect to the average primary particle diameter. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-80503 A [Patent Document 2] JP 2016-68037 A [Patent Document 3] JP 2016-190980 A Summary of the Invention [Problem to be solved by the invention]
[0007] In hollow particles used as additives for molded bodies, in order to improve the effects of weight reduction, heat insulation, opacity, etc. of the molded body, it is desired to increase the porosity of the hollow particles to be blended and to make the hollow particles less likely to be crushed when kneading with other materials and when molding after kneading. However, it has been difficult to achieve both high porosity and strength in hollow particles. If the hollow particles added to the molded body are crushed, the weight reduction of the molded body by the hollow particles is not realized. Furthermore, conventional hollow particles have a problem that volatile compounds such as poorly water-soluble solvents used in the manufacturing process and unreacted polymerizable monomers tend to remain in the particles. When a molded body is produced using a resin composition containing hollow particles with a high content of volatile compounds, there is a risk that the volatile compounds in the hollow particles will volatilize and cause foaming or fire when the resin composition is kneaded. In addition, compared to hollow particles with a low content of volatile compounds, hollow particles with a high content of volatile compounds have a high specific gravity, so there is also a problem that the efficiency of weight reduction is inferior. The hollow polymeric microparticles described in Patent Document 1 have a problem in that, due to their thick shell, volatile compounds such as poorly water-soluble solvents used in the production process tend to remain in the particles. The hollow resin particles described in Patent Document 2 have a problem in that the shell has low strength because the proportion of crosslinkable monomer units contained in the shell is small. The hollow resin particles described in Patent Document 3 have fine through holes, so when an attempt is made to produce a molded body using a resin composition containing these hollow resin particles, the resin penetrates into the hollow resin particles through the through holes during molding, making it difficult to maintain the voids in the hollow resin particles, and therefore it is difficult to reduce the weight of the molded body.
[0008] An object of the present disclosure is to provide hollow particles that have a high porosity, are resistant to crushing, and have a reduced content of volatile compounds, a resin composition containing the hollow particles and a resin, and a molded article of the resin composition. [Means for solving the problem]
[0009] The present inventors have noticed that in order to make hollow particles less susceptible to crushing and to reduce the content of volatile compounds in the hollow particles, it is important that the composition of the shell of the hollow particles is balanced, that the hollow particles have a moderate porosity, and that the shell thickness is adequate.
[0010] According to the present disclosure, there is provided a hollow particle having a shell and a hollow portion surrounded by the shell, the hollow particle having a porosity of 50% or more and 90% or less, The shell has a thickness of 0.2 μm or more and 0.9 μm or less, and contains a polymer derived from a polymerizable monomer for the shell consisting of 70% by mass or more and 100% by mass or less of a crosslinkable monomer and 0% by mass or more and 30% by mass or less of a non-crosslinkable monomer, and a polar resin selected from the group consisting of polymers containing a repeating unit containing a heteroatom.
[0011] In the hollow particles of the present disclosure, the content of the polar resin is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the polymerizable monomer for shell.
[0012] In the hollow particles of the present disclosure, the polar resin is preferably an acrylic resin.
[0013] In the hollow particles of the present disclosure, the acrylic resin, which is the polar resin, is preferably a copolymer derived from a polymerizable monomer for polar resin, which contains 50.0% by mass or more and 99.9% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of a polar group-containing monomer containing at least one polar group selected from a carboxyl group, a hydroxyl group, a sulfonic acid group, an amino group, a polyoxyethylene group, and an epoxy group.
[0014] According to the present disclosure, there is provided a resin composition containing the hollow particles of the present disclosure and a resin. Further, according to the present disclosure, there is provided a molded article of the resin composition of the present disclosure. Effect of the Invention
[0015] According to the present disclosure as described above, it is possible to provide hollow particles that have a high porosity, are resistant to crushing, and have a reduced content of volatile compounds, a resin composition containing the hollow particles and a resin, and a molded article of the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] I. Hollow particles The hollow particles of the present disclosure are particles having a shell (outer shell) containing a resin and a hollow portion surrounded by the shell. In the present disclosure, the hollow portion is a hollow space that is clearly distinguished from the shell of the hollow particle formed of a resin material. The shell of the hollow particle may have a porous structure, but in that case, the hollow portion has a size that is clearly distinguishable from the numerous minute spaces uniformly distributed within the porous structure. The hollow portion of the hollow particles can be confirmed, for example, by SEM observation of the cross section of the particle or by TEM observation of the particle itself. The hollow portion of the hollow particles may be filled with a gas such as air, or may contain a solvent. In addition, the hollow particles of the present disclosure usually have a shell that does not have a through hole or a shell defect, and the hollow part is isolated from the outside of the particle by the shell. In general, hollow particles include those in which the shell does not have a through hole that connects the hollow part to the outside space of the particle, and those in which the shell has one or more through holes and the hollow part is connected to the outside of the particle through the through hole. Although the through hole may impart a useful function to the hollow particle, it also causes the strength of the hollow particle to be reduced and makes it more likely to be crushed because it is a part where the shell is missing. The hollow particles of the present disclosure usually do not have through holes with a diameter of 10 nm or more and 500 nm or less. In addition, in the present disclosure, the shell defect of the hollow particle means a crack-like defect that is extremely large compared to the size of the particle, and causes the strength of the hollow particle to deteriorate. Although it depends on the size of the hollow particle, a crack having a length of 1 μm or more is generally recognized as a shell defect because it significantly deteriorates the strength of the hollow particle. In the present disclosure, the shell being free of interconnecting pores and shell defects means that the shell is substantially free of interconnecting pores and shell defects. When 100 hollow particles are observed using an SEM, if 5 or fewer hollow particles have interconnecting pores or shell defects, the shell is deemed to have no interconnecting pores or shell defects.
[0017] The hollow particles according to the present disclosure include a shell and a hollow portion surrounded by the shell, and have a porosity of 50% or more and 90% or less, The shell has a thickness of 0.2 μm or more and 0.9 μm or less, and is characterized in that it contains a polymer derived from a polymerizable monomer for the shell consisting of 70% by mass or more and 100% by mass or less of a crosslinkable monomer and 0% by mass or more and 30% by mass or less of a non-crosslinkable monomer, and a polar resin selected from the group consisting of polymers containing a repeating unit containing a heteroatom.
[0018] The hollow particles of the present disclosure are produced, for example, by a suspension polymerization method in which a mixture containing the specific amount of crosslinkable monomer, the non-crosslinkable monomer that may be added in the specific amount, a polar resin that has been polymerized in advance, an oil-soluble polymerization initiator, and a hydrocarbon solvent is dispersed in an aqueous medium and then polymerized. In the hollow particles of the present disclosure, a polymer formed by polymerizing a polymerizable monomer for a shell consisting of the specific amount of crosslinkable monomer and the non-crosslinkable monomer that may be added in the specific amount forms the skeleton of the shell, and the polar resin that is added in a prepolymerized state is usually attached to the surface of the polymer. When the hollow particles of the present disclosure are produced by the suspension polymerization method, the polymerization reaction proceeds in a state in which droplets containing the crosslinkable monomer and the polar resin are dispersed in an aqueous medium. The polar resin in the droplets has a relatively high affinity with the aqueous medium and is easily moved to the interface with the aqueous medium. Therefore, it is presumed that the hollow particles of the present disclosure obtained after the polymerization reaction have a polar resin easily arranged on the outer surface of the shell. In the hollow particles of the present disclosure, the proportion of crosslinkable monomer units in the polymer derived from the shell polymerizable monomer that forms the shell is 70 mass% or more, and therefore the content of crosslinkable monomer units in the shell of the hollow particles is sufficiently high, so that a covalent bond network is densely spread throughout the shell, resulting in excellent strength, resistance to crushing, and resistance to deformation even when exposed to heat or the like applied from the outside. In addition, the shell of the hollow particles of the present disclosure contains a polar resin, so that the shell thickness is likely to be 0.2 μm or more and 0.9 μm or less. The hollow particles of the present disclosure are typically obtained by a method using an inorganic dispersant in the suspension process (granulation process). In the suspension process, the heteroatoms of the polar resin are present on the droplet surface, which improves the affinity between the droplets and the inorganic dispersant, making it easier for the inorganic dispersant to cover the droplets, resulting in droplets of an appropriate particle size. Furthermore, it is estimated that the shell thickness of the hollow particles is 0.2 μm or more and 0.9 μm or less by adjusting the amount of the hydrocarbon solvent contained in the droplets so that the porosity is 50% or more and 90% or less. In addition, the hollow particles of the present disclosure obtained by such a method usually do not have a shell with continuous holes or shell defects. The hollow particles of the present disclosure have a high porosity of 50% or more and 90% or less, and therefore have excellent lightness. In addition, the hollow particles of the present disclosure have a shell with a skeleton having excellent strength, a moderate shell thickness of 0.2 μm or more and 0.9 μm or less, and preferably have no interconnected holes or shell defects, so that the shell has excellent strength. Therefore, the hollow particles of the present disclosure can achieve both lightness and strength, and are difficult to be crushed when kneaded with other materials such as resins, or when molded after kneading with resins, etc., and can be used as a lightweight material. Furthermore, the hollow particles of the present disclosure have a porosity of 50% or more and 90% or less, and a shell thickness of 0.2 μm or more and 0.9 μm or less, which is appropriately thin, and therefore, in the manufacturing process, volatile compounds such as poorly water-soluble solvents and unreacted polymerizable monomers in the particles can be easily removed, and the content of volatile compounds can be easily reduced. Since the hollow particles of the present disclosure have a reduced content of volatile compounds, when a resin composition containing the hollow particles of the present disclosure is kneaded, there is no risk of foaming or ignition due to the volatile compounds in the hollow particles, and the specific gravity is lighter than that of hollow particles with a high content of volatile compounds, and therefore the efficiency of weight reduction is excellent. In the present disclosure, the volatile compound refers to a compound that volatilizes when the resin composition containing the hollow particles of the present disclosure is kneaded, and typically refers to a compound that volatilizes when the resin composition containing the hollow particles of the present disclosure is melt-kneaded. The volatile compound is usually a compound having a boiling point of 235° C. or less and a molecular weight of 200 or less. The volatile compound contained in the hollow particles is typically a hydrocarbon solvent used in the production of the hollow particles and an unreacted polymerizable monomer remaining in the particles. The materials, physical properties, and applications of the hollow particles of the present disclosure, as well as the method for producing the hollow particles of the present disclosure, will be described in detail below.
[0019] (1) Polymer derived from polymerizable monomer for shell The shell of the hollow particle of the present disclosure contains a polymer derived from a polymerizable monomer for the shell, which comprises 70% by mass or more and 100% by mass or less of a crosslinkable monomer and 0% by mass or more and 30% by mass or less of a non-crosslinkable monomer. Here, the polymer derived from the polymerizable monomer for the shell is a polymer obtained by polymerization of the polymerizable monomer for the shell, and forms the skeleton of the shell of the hollow particle of the present disclosure. In the present disclosure, a polymerizable monomer is a compound having a polymerizable functional group. A non-crosslinkable monomer is a polymerizable monomer having only one polymerizable functional group, and a crosslinkable monomer is a polymerizable monomer having two or more polymerizable functional groups and capable of forming a crosslinked bond in a resin by a polymerization reaction. As the polymerizable monomer, a compound having an ethylenically unsaturated bond as a polymerizable functional group is generally used.
[0020] [Cross-linking monomer] Since the crosslinkable monomer has a plurality of polymerizable functional groups, the monomers can be linked together, and the strength and heat resistance of the shell can be increased. Examples of the crosslinkable monomer include difunctional crosslinkable monomers such as divinylbenzene, divinyldiphenyl, divinylnaphthalene, diallyl phthalate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate; and trifunctional or higher crosslinkable monomers such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among these, divinylbenzene, ethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate are preferred, and ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate are more preferred. These crosslinkable monomers can be used alone or in combination of two or more kinds. In the present disclosure, (meth)acrylate means either acrylate or methacrylate, and (meth)acrylic means either acrylic or methacrylic.
[0021] [Non-crosslinkable monomer] As the non-crosslinkable monomer, a monovinyl monomer is preferably used. A monovinyl monomer is a compound having one polymerizable vinyl functional group. Examples of the monovinyl monomer include (meth)acrylic monovinyl monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, glycidyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; aromatic vinyl monomers such as styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, and halogenated styrene; monoolefin monomers such as ethylene, propylene, and butylene; (meth)acrylamide monomers and derivatives thereof such as (meth)acrylamide, N-methylol (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; diene monomers such as butadiene and isoprene; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated vinyl monomers such as vinyl chloride; halogenated vinylidene monomers such as vinylidene chloride; and vinylpyridine monomers. Among them, the monovinyl monomer is preferably a (meth)acrylic monovinyl monomer from the viewpoint of reactivity, and more preferably at least one selected from butyl acrylate and methyl methacrylate. These non-crosslinkable monomers can be used alone or in combination of two or more kinds.
[0022] In the present disclosure, the content ratio of the crosslinkable monomer and the non-crosslinkable monomer in 100% by mass of the polymerizable monomer for the shell is 70% by mass or more and 100% by mass or less for the crosslinkable monomer, and 0% by mass or more and 30% by mass or less for the non-crosslinkable monomer. When the content ratio of the crosslinkable monomer is 70% by mass or more, the content ratio of the crosslinkable monomer unit in the shell of the hollow particle is sufficiently high, and a covalent bond network is densely spread throughout the shell, resulting in excellent strength, being difficult to crush, and being difficult to deform even when exposed to heat or the like applied from the outside. On the other hand, when the non-crosslinkable monomer is contained at a ratio of 30% by mass or less, the occurrence of shell interconnections and shell defects is further easily suppressed. In addition, when the polymerizable monomer for the shell contains the non-crosslinkable monomer, the content ratio of the crosslinkable monomer and the non-crosslinkable monomer in 100% by mass of the polymerizable monomer for the shell is not particularly limited, and may be, for example, 70% by mass or more and 95% by mass or less of the crosslinkable monomer and 5% by mass or more and 30% by mass or less of the non-crosslinkable monomer, or 70% by mass or more and 90% by mass or less of the crosslinkable monomer and 10% by mass or more and 30% by mass or less of the non-crosslinkable monomer.
[0023] (2) Polar resin The shell of the hollow particles of the present disclosure further comprises a polar resin. In the present disclosure, the polar resin is selected from the group consisting of polymers containing a repeating unit containing a heteroatom. Specific examples of the polar resin include acrylic resins, polyester resins, and vinyl resins containing a heteroatom. The polar resin may be a homopolymer or copolymer of a heteroatom-containing monomer, or a copolymer of a heteroatom-containing monomer and a non-heteroatom-containing monomer. When the polar resin is a copolymer of a heteroatom-containing monomer and a non-heteroatom-containing monomer, the ratio of the heteroatom-containing monomer unit in 100% by mass of all repeating units constituting the copolymer is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, from the viewpoint of easy control of the particle diameter and shell thickness of the hollow particles.
[0024] Examples of heteroatom-containing monomers used in polar resins include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, acrylic acid, methacrylic acid, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, glycidyl (meth)acrylate, 4-hydroxybutyl Examples of the monomers include monomers having a (meth)acryloyl group, such as acrylate glycidyl ether, i.e., (meth)acrylic monovinyl monomers; aromatic vinyl monomers containing heteroatoms, such as halogenated styrene and styrene sulfonic acid; vinyl carboxylate ester monomers, such as vinyl acetate; halogenated vinyl monomers, such as vinyl chloride; halogenated vinylidene monomers, such as vinylidene chloride; vinylpyridine monomers; carboxyl group-containing monomers, such as ethylenically unsaturated carboxylic acid monomers, such as crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid; and epoxy group-containing monomers, such as allyl glycidyl ether. These heteroatom-containing monomers may be used alone or in combination of two or more. Examples of heteroatom-free monomers used in polar resins include aromatic vinyl monomers not containing heteroatoms, such as styrene, vinyltoluene, α-methylstyrene, and p-methylstyrene; monoolefin monomers, such as ethylene, propylene, and butylene; and diene monomers, such as butadiene and isoprene. These heteroatom-free monomers can be used alone or in combination of two or more.
[0025] In particular, the polar resin is preferably an acrylic resin in which the total mass of (meth)acrylic monovinyl monomer units is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, of all repeating units constituting the resin (100 mass%), from the viewpoints of high compatibility with the polymerizable monomer for the shell and easy control of the particle size of the hollow particles and the thickness of the shell. In particular, it is preferable that the polar resin is an acrylic resin in which all repeating units constituting the resin are composed of (meth)acrylic monovinyl monomer units.
[0026] In the polar resin, the heteroatom-containing monomer preferably contains a polar group-containing monomer unit containing at least one polar group selected from a carboxyl group, a hydroxyl group, a sulfonic acid group, an amino group, a polyoxyethylene group, and an epoxy group, because it is easy to control the particle size and shell thickness of the hollow particles. As the polar group, at least one selected from a carboxyl group and a hydroxyl group is preferable because it is possible to control the particle size with a small amount of addition. Examples of polar group-containing monomers include carboxyl group-containing monomers such as ethylenically unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; sulfonic acid group-containing monomers such as styrenesulfonic acid; amino group-containing monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; polyoxyethylene group-containing monomers such as methoxypolyethylene glycol (meth)acrylate; and epoxy group-containing monomers such as glycidyl (meth)acrylate, allyl glycidyl ether, and 4-hydroxybutyl acrylate glycidyl ether. These polar group-containing monomers can be used alone or in combination of two or more. When the polar resin contains a polar group-containing monomer unit, it is preferable that the polar group is located at the end of the main chain or side chain, or is bonded in a pendant manner to the main chain or side chain, since this makes it easier for the polar resin to be positioned on the outer surface of the hollow particle and makes it easier to control the particle size and shell thickness of the hollow particle.
[0027] When the polar resin does not contain the polar group-containing monomer unit, the heteroatom-containing monomer unit contained in the polar resin preferably contains a monomer unit derived from an alkyl(meth)acrylate, from the viewpoints of high compatibility with the polymerizable monomer for the shell and ease of control of the particle size and shell thickness of the hollow particles, and among these, from the viewpoint of high polarity, it is preferable to contain a monomer unit derived from an alkyl(meth)acrylate, preferably having an alkyl group with 3 or less carbon atoms, more preferably having an alkyl group being a methyl group or ethyl group, and even more preferably having an alkyl group being a methyl group.
[0028] The acrylic resin, which is the polar resin, is preferably a polymer or copolymer derived from a polymerizable monomer for polar resin containing 50.0% by mass or more of methyl methacrylate when the total mass of the polymerizable monomer for polar resin is taken as 100% by mass, because it has high compatibility with the polymerizable monomer for shell and is easy to control the particle size of the hollow particles and the thickness of the shell. In this disclosure, the polymerizable monomer used in the synthesis of the polar resin is referred to as the polymerizable monomer for polar resin. The acrylic resin as the polar resin is more preferably a copolymer of a polymerizable monomer for a polar resin containing 50.0% by mass or more and 99.9% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, from the viewpoint of easier control of the particle diameter and shell thickness of the hollow particles, still more preferably a copolymer of a polymerizable monomer for a polar resin containing 50.0% by mass or more and 99.0% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, and ... 50.0% by mass or more and 98.0% by mass or less of methyl methacrylate. and a copolymer of polymerizable monomers for polar resins, the copolymer comprising 50.0% by mass or more and 98.0% by mass or less of methyl methacrylate, 1.0% by mass or more and 5.0% by mass or less of a (meth)acrylic monovinyl monomer different from methyl methacrylate and not containing the polar group, and 0.1% by mass or more and 5.0% by mass or less of the polar group-containing monomer, and particularly preferably a copolymer of polymerizable monomers for polar resins, the copolymer comprising 50.0% by mass or more and 98.0% by mass or less of methyl methacrylate, 1.0% by mass or more and 5.0% by mass or less of a (meth)acrylic monovinyl monomer different from methyl methacrylate and not containing the polar group, and 0.2% by mass or more and 3.0% by mass or less of the polar group-containing monomer. The (meth)acrylic monovinyl monomer which is different from methyl methacrylate and does not contain a polar group is preferably at least one selected from ethyl acrylate and butyl acrylate, and particularly preferably ethyl acrylate, in terms of being able to control the glass transition temperature. As the polar group-containing monomer, from the viewpoint of compatibility with the polymerizable monomer for the shell, a (meth)acrylic monovinyl monomer containing a polar group is preferred, and from the viewpoint of the particle size control with a smaller addition amount, a (meth)acrylic monovinyl monomer containing a carboxyl group or a hydroxyl group is more preferred.
[0029] The polar resin can be obtained, for example, by polymerizing a polymerizable monomer for polar resins containing the heteroatom-containing monomer by a polymerization method such as solution polymerization or emulsion polymerization. Furthermore, when the polar resin is a copolymer, the copolymer may be any of a random copolymer, a block copolymer, or a graft copolymer, but is preferably a random copolymer. In addition, the polar resin is preferably pulverized as finely as possible in order to improve the solubility.
[0030] The number average molecular weight (Mn) of the polar resin is not particularly limited, but is preferably in the range of 3000 to 20000, more preferably in the range of 4000 to 17000, and even more preferably in the range of 6000 to 15000, in terms of polystyrene, measured by gel permeation chromatography (GPC) using tetrahydrofuran. When the number average molecular weight (Mn) of the polar resin is equal to or more than the lower limit, the solubility of the polar resin is improved, and the particle size and shell thickness of the hollow particles can be easily controlled, and when it is equal to or less than the upper limit, a decrease in the strength of the shell can be suppressed.
[0031] In the hollow particles of the present disclosure, the content of the polar resin is preferably 0.1 parts by mass or more and 10.0 parts by mass or less, more preferably 0.3 parts by mass or more and 8.0 parts by mass or less, and even more preferably 0.5 parts by mass or more and 8.0 parts by mass or less, relative to 100 parts by mass of the shell polymerizable monomer. When the content of the polar resin is equal to or more than the lower limit, it is easy to control the particle diameter and shell thickness of the hollow particles, so that the strength of the hollow particles can be improved and the content of volatile compounds can be reduced. On the other hand, when the content of the polar resin is equal to or less than the upper limit, it is possible to suppress the decrease in the content ratio of the polymer derived from the shell polymerizable monomer, so that the decrease in the strength of the shell can be suppressed and the collapse of the hollow particles can be further suppressed.
[0032] (3) Physical properties of hollow particles The hollow particles of the present disclosure have a porosity of 50% or more and 90% or less, preferably 50% or more and 85% or less, and more preferably 60% or more and 80% or less. By having a porosity of the above lower limit or more, the hollow particles are excellent in lightness, heat resistance, and heat insulation, and the poorly water-soluble solvent used in the polymerization process is less likely to remain inside the particles. In addition, by having a porosity of the above upper limit or less, the hollow particles are less likely to be crushed and have excellent strength. The porosity of the hollow particles can be adjusted by the amount of the hydrocarbon solvent in the mixed solution, for example, when the hollow particles are produced by the suspension polymerization method described later. In the suspension polymerization method described later, the polymerization reaction proceeds in a state in which the oil droplets containing the crosslinkable monomer and the like contain the hydrocarbon solvent, so that the porosity of the obtained hollow particles tends to increase as the content of the hydrocarbon solvent increases.
[0033] The porosity of the hollow particles of the present disclosure is determined by the apparent density D 1 and true density D 0 It is calculated from: Apparent density of hollow particles D 1 The measurement method is as follows. First, a volume of 100 cm 3 30 cm into a measuring flask 3 The hollow particles are filled into the measuring flask, and the mass of the filled hollow particles is accurately weighed. Next, the measuring flask filled with the hollow particles is accurately filled with isopropanol up to the marked line, while being careful not to introduce air bubbles. The mass of isopropanol added to the measuring flask is accurately weighed, and the apparent density D of the hollow particles is calculated based on the following formula (I). 1 (g / cm 3 ) to calculate Formula (I) Apparent density D 1 = [Mass of hollow particles] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at measurement temperature]) Apparent density D 1 corresponds to the specific gravity of the entire hollow particle when the hollow portion is considered to be a part of the hollow particle.
[0034] Hollow particle true density D 0The measurement method is as follows: After crushing the hollow particles in advance, 3 The measuring flask is filled with about 10 g of crushed pieces of hollow particles, and the mass of the crushed pieces is accurately weighed. Then, in the same manner as in the measurement of the apparent density above, isopropanol is added to the measuring flask, the mass of isopropanol is accurately weighed, and the true density D of the hollow particles is calculated based on the following formula (II). 0 (g / cm 3 ) to calculate Formula (II) true density D 0 = [Mass of crushed hollow particle pieces] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at the measurement temperature]) true density D 0 corresponds to the specific gravity of only the shell part of the hollow particle. As is clear from the above measurement method, the true density D 0 In calculating the diameter of the hollow particles, the hollow portion is not considered to be part of the hollow particle.
[0035] The porosity (%) of a hollow particle is the apparent density D 1 and true density D 0 It is calculated by the following formula (III). Formula (III) Porosity (%) = 100 - (apparent density D 1 / true density D 0 ) x 100 The porosity of a hollow particle can be expressed as the proportion of the hollow portion in the specific gravity of the hollow particle.
[0036] The lower limit of the volume average particle diameter (Dv) of the hollow particles of the present disclosure is preferably 4.0 μm or more, more preferably 4.5 μm or more, and even more preferably 5.0 μm or more. On the other hand, the upper limit of the volume average particle diameter (Dv) of the hollow particles of the present disclosure is preferably 25.0 μm or less, more preferably 13.0 μm or less, even more preferably 12.0 μm or less, and particularly preferably 10.0 μm or less. When the volume average particle diameter of the hollow particles is equal to or greater than the lower limit, the hollow particles are less likely to aggregate with each other, and therefore excellent dispersibility can be exhibited. When the volume average particle diameter of the hollow particles is equal to or less than the upper limit, the mechanical strength is improved.
[0037] The particle size distribution of the hollow particles (volume average particle size (Dv) / number average particle size (Dn)) may be, for example, 1.1 or more and 2.5 or less. When the particle size distribution is 2.5 or less, particles with little variation in compressive strength characteristics and heat resistance between particles can be obtained. In addition, when a sheet-shaped molded product is produced, for example, a product with a uniform thickness can be produced by the particle size distribution being 2.5 or less. The volume average particle diameter (Dv) and number average particle diameter (Dn) of the hollow particles can be determined, for example, by measuring the particle diameter of the hollow particles using a laser diffraction particle size distribution analyzer, calculating the number average and volume average, and using the obtained values as the number average particle diameter (Dn) and volume average particle diameter (Dv) of the particles. The particle size distribution is determined by dividing the volume average particle diameter by the number average particle diameter.
[0038] The hollow particles of the present disclosure may also have an average circularity of 0.950 or more and 0.995 or less. The shape of the hollow particles can be confirmed, for example, by SEM or TEM. The internal shape of the hollow particles can be confirmed by SEM or TEM after cutting the particles into slices by a known method.
[0039] In addition, the hollow particles of the present disclosure have a shell thickness of 0.2 μm or more and 0.9 μm or less, preferably 0.2 μm or more and 0.8 μm or less, more preferably 0.25 μm or more and 0.7 μm or less, even more preferably 0.25 μm or more and 0.6 μm or less, and even more preferably 0.25 μm or more and 0.5 μm or less. The shell thickness of the hollow particles can be calculated by calculating the inner diameter r of the hollow particles according to the following formula (1) using the volume average particle diameter R and porosity of the hollow particles, and then calculating the inner diameter r and the volume average particle diameter R according to the following formula (2). 4 / 3π×(R / 2) 3×Porosity=4 / 3π×(r / 2) 3 Formula (1) Shell thickness = (Rr) / 2 Equation (2) The difference between the shell thickness calculated in this manner and the average thickness measured at 20 points on the shell is usually within ±10% of these average values, so the shell thickness calculated as described above can be regarded as the shell thickness of the hollow particles. The thickness at each point of the shell of a hollow particle used to calculate the average thickness at 20 points on the shell can be measured, for example, by breaking a hollow particle and observing a piece of the shell with an SEM.
[0040] In addition, the content of the volatile compound in the hollow particles of the present disclosure is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0.2% by mass or less, based on 100% by mass of the total mass of the hollow particles. By having the content of the volatile compound in the hollow particles be equal to or less than the upper limit, there is no risk of the volatile compound in the hollow particles volatilizing and causing foaming or ignition when the hollow particles of the present disclosure are kneaded with other materials, and the specific gravity of the hollow particles can be reduced, thereby improving the effect as a lightweight material. The content of volatile compounds in hollow particles is measured by the following method. First, about 100 mg of hollow particles are placed in a 30 mL screw-top glass bottle and weighed accurately. Next, about 10 g of tetrahydrofuran (THF) is placed in the bottle and weighed accurately. The mixture in the glass bottle is stirred with a stirrer for 1 hour to extract the volatile compounds contained in the hollow particles. The stirring is stopped, the resin components of the hollow particles that are insoluble in THF are allowed to settle, and the precipitate is filtered to obtain a sample liquid. The sample liquid is analyzed by gas chromatography (GC), and the amount of volatile compounds (mass%) contained in the hollow particles per unit mass is determined from the GC peak area and a calibration curve created in advance. The detailed analysis conditions are as follows: (Analysis conditions) Equipment: GC-2010 (Shimadzu Corporation) Column: DB-5 (Agilent Technologies, Inc.) Film thickness 0.25μm, inner diameter 0.25mm, length 30m Detector: FID Carrier gas: Nitrogen (linear velocity: 28.8 cm / sec) Inlet temperature: 200℃ Detector temperature: 250℃ Oven temperature: Increase from 40°C to 230°C at a rate of 10°C / min, and hold at 230°C for 2 minutes. Sampling volume: 2μL
[0041] (4)Applications The hollow particles of the present disclosure are particularly suitable as additives for molded bodies because they are difficult to crush when kneaded with other materials and when molded after kneading, and when added to a molded body, they have excellent effects as a weight-reducing material, heat insulating material, soundproofing material, vibration-damping material, etc. The hollow particles of the present disclosure are particularly suitable as additives for resin molded bodies because they are difficult to crush when kneaded with resin and when molded after kneading. Examples of resin molded bodies containing the hollow particles of the present disclosure include light reflecting materials, heat insulating materials, sound insulating materials, low dielectric materials, and food containers used in various fields such as automobiles, electricity, electronics, architecture, aviation, and space. In addition, the hollow particles of the present disclosure have a high porosity, are not easily crushed, and have excellent heat resistance, so that they meet the heat insulation and shock-absorbing properties (cushioning properties) required for undercoat materials and also meet the heat resistance required for thermal paper applications. In addition, the hollow particles of the present disclosure are also useful as plastic pigments with excellent gloss, hiding power, etc. Furthermore, the hollow particles of the present disclosure can be obtained by encapsulating useful ingredients such as fragrances, medicines, agricultural chemicals, and ink ingredients inside the particles by means of immersion treatment, reduced pressure or pressurized immersion treatment, or the like, and therefore can be used for various purposes depending on the ingredients contained inside.
[0042] (5) Manufacturing method of hollow particles The method for producing the hollow particles of the present disclosure is not particularly limited as long as the method can produce the hollow particles of the present disclosure. Hereinafter, one embodiment of the method for producing hollow particles will be described, but the method for producing hollow particles of the present disclosure is not necessarily limited to the following embodiment.
[0043] One embodiment of the method for producing hollow particles according to the present disclosure includes: A mixed solution preparation step of preparing a mixed solution containing a shell polymerizable monomer, a polar resin, a hydrocarbon-based solvent, a dispersant, and an aqueous medium; a suspending step of preparing a suspension in which droplets of a monomer composition containing a hydrocarbon solvent (sometimes referred to as polymerizable monomer droplets in the present disclosure) are dispersed in an aqueous medium by suspending the mixed liquid; and a polymerization step of subjecting the suspension to a polymerization reaction. The method for producing hollow particles may further include, after the polymerization step, a solvent removal step of removing the hydrocarbon solvent encapsulated in the particles.
[0044] In the present disclosure, the hollow particles encapsulating the hydrocarbon solvent obtained by the polymerization step may be considered as intermediates of the hollow particles of the present disclosure and may be referred to as precursor particles. Also, in the present disclosure, a composition containing the precursor particles is referred to as a precursor composition. The above four steps and other steps will be described below in order.
[0045] (A) Mixed liquid preparation process This step is a step of preparing a mixed liquid containing a polymerizable monomer for the shell, a polar resin, a hydrocarbon-based solvent, a dispersant, and an aqueous medium. In this step, an oil phase containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon solvent, and an aqueous phase containing a dispersant and an aqueous medium are usually prepared separately in advance, and then mixed to prepare a mixed liquid, which allows hollow particles having a uniform shell composition to be produced. The oil phase used in preparing the mixed liquid usually further contains an oil-soluble polymerization initiator as a polymerization initiator.
[0046] The polymerizable monomer for shell and the polar resin to be contained in the mixture obtained in the mixture preparation step are as described above. The content of the shell polymerizable monomer in the mixed solution is not particularly limited, but from the viewpoint of the balance between the porosity, particle size, and mechanical strength of the hollow particles, and from the viewpoint of reducing the residual amount of the hydrocarbon solvent, the total content of the shell polymerizable monomer is preferably 15 parts by mass or more and 55 parts by mass or less, and more preferably 25 parts by mass or more and 40 parts by mass or less, per 100 parts by mass of the total mass of the components in the mixed solution excluding the aqueous medium.
[0047] [Hydrocarbon solvents] In this production method, a hydrocarbon-based solvent is used as the non-polymerizable and poorly water-soluble organic solvent. The hydrocarbon solvent has the function of forming a hollow portion inside the particle. In the suspension process described later, a suspension is obtained in which polymerizable monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium. In the suspension process, phase separation occurs in the polymerizable monomer droplets, and as a result, the hydrocarbon solvent with low polarity tends to gather inside the polymerizable monomer droplets. Finally, in the polymerizable monomer droplets, the hydrocarbon solvent is distributed inside the droplets and other materials other than the hydrocarbon solvent are distributed around the droplets according to their respective polarities. Then, in the polymerization process described later, a precursor composition is obtained that includes precursor particles containing the hydrocarbon solvent. That is, the hydrocarbon solvent gathers inside the particles, and a hollow portion filled with the hydrocarbon solvent is formed inside the obtained precursor particles.
[0048] The hydrocarbon solvent used in the production method of the present disclosure preferably contains a saturated hydrocarbon solvent in a total amount of 100% by mass. This allows sufficient phase separation to occur in the polymerizable monomer droplets, making it easy to obtain hollow particles having only one hollow portion, and suppressing the generation of porous particles. The ratio of the saturated hydrocarbon solvent is preferably 60% by mass or more, more preferably 80% by mass or more, in order to further suppress the generation of porous particles and to make the hollow portions of each hollow particle uniform.
[0049] Examples of the saturated hydrocarbon solvent contained in the hydrocarbon solvent include butane, pentane, normal hexane, cyclohexane, heptane, and octane. As the hydrocarbon solvent other than the saturated hydrocarbon solvent, for example, aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc. can be preferably used.
[0050] Moreover, the hydrocarbon solvent is preferably a hydrocarbon solvent having a carbon number of 4 to 7. A hydrocarbon compound having a carbon number of 4 to 7 is easily encapsulated in the precursor particles during the polymerization step, and can be easily removed from the precursor particles during the solvent removal step. Among them, a hydrocarbon solvent having a carbon number of 5 or 6 is particularly preferred.
[0051] Although not particularly limited, the hydrocarbon solvent preferably has a boiling point of 130° C. or less, more preferably 100° C. or less, in order to be easily removed in the solvent removal step described below. Moreover, the hydrocarbon solvent preferably has a boiling point of 50° C. or more, more preferably 60° C. or more, in order to be easily encapsulated in the precursor particles.
[0052] In addition, the hydrocarbon solvent preferably has a relative dielectric constant of 3 or less at 20°C. The relative dielectric constant is one of the indices that indicate the polarity of a compound. When the relative dielectric constant of the hydrocarbon solvent is sufficiently small, 3 or less, it is considered that phase separation proceeds quickly in the polymerizable monomer droplets, and hollow spaces are easily formed. Examples of solvents with a dielectric constant of 3 or less at 20°C are as follows. The value in parentheses is the dielectric constant value. Heptane (1.9), cyclohexane (2.0), benzene (2.3), toluene (2.4), octane (1.9). For the relative dielectric constant at 20°C, values described in known documents (for example, "Chemical Handbook Basic Edition" edited by the Chemical Society of Japan, revised 4th edition, Maruzen Co., Ltd., published on September 30, 1993, pages II-498 to II-503) and other technical information can be referenced. Examples of methods for measuring the relative dielectric constant at 20°C include a relative dielectric constant test performed in accordance with JISC 2101:1999, Section 23, at a measurement temperature of 20°C.
[0053] In the present disclosure, the content of the hydrocarbon solvent in the mixed solution is preferably 50 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the total mass of the shell polymerizable monomer, because it is easy to control the particle size of the hollow particles, it is easy to increase the porosity while maintaining the strength of the hollow particles, and it is easy to reduce the amount of residual hydrocarbon solvent in the particles. The content of the hydrocarbon solvent in the mixed solution is preferably 60 parts by mass or more and 400 parts by mass or less, more preferably 70 parts by mass or more and 300 parts by mass or less, and even more preferably 80 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the total mass of the shell polymerizable monomer.
[0054] [Oil-soluble polymerization initiator] The mixed liquid preferably contains an oil-soluble polymerization initiator as a polymerization initiator. The oil-soluble polymerization initiator is not particularly limited as long as it is lipophilic and has a solubility in water of 0.2% by mass or less. Examples of the oil-soluble polymerization initiator include benzoyl peroxide, lauroyl peroxide, t-butyl peroxide-2-ethylhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile.
[0055] The content of the oil-soluble polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and even more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the total mass of the shell polymerizable monomers in the mixed solution. By having the content of the oil-soluble polymerization initiator within the above range, the polymerization reaction can be sufficiently progressed, and there is little risk of the oil-soluble polymerization initiator remaining after completion of the polymerization reaction, and there is also little risk of an unexpected side reaction proceeding.
[0056] [Dispersant] The dispersant contained in the mixed liquid is a dispersant contained in the aqueous phase, and an inorganic dispersant is preferably used. By using an inorganic dispersant, it is possible to form polymerizable monomer droplets having a large particle size in the suspension, and the shell thickness after polymerization is likely to be 0.2 μm or more and 0.9 μm or less, and the crushing of the obtained hollow particles is likely to be suppressed. In addition, by using an inorganic dispersant, it is possible to narrow the particle size distribution of the hollow particles, and further, the amount of the dispersant remaining after washing can be reduced. Examples of the inorganic dispersant include inorganic compounds such as sulfates, such as barium sulfate and calcium sulfate; carbonates, such as barium carbonate, calcium carbonate and magnesium carbonate; phosphates, such as calcium phosphate; metal oxides, such as aluminum oxide and titanium oxide; metal hydroxides, such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide and ferric hydroxide. These dispersants can be used alone or in combination of two or more. Among the above dispersants, the above-mentioned poorly water-soluble inorganic metal salts such as sulfates, carbonates, phosphates, and metal hydroxides are preferred, metal hydroxides are more preferred, and magnesium hydroxide is particularly preferred. In the present disclosure, the poorly water-soluble inorganic metal salt is preferably an inorganic metal salt having a solubility of 0.5 g or less in 100 g of water.
[0057] The content of the dispersant is not particularly limited, but is usually 0.5 parts by mass to 10 parts by mass, and preferably 1 part by mass to 8 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer for shell and the hydrocarbon solvent. By having the content of the dispersant within the above range, the thickness of the shell after polymerization is likely to be 0.2 μm to 0.9 μm, and the crushing of the obtained hollow particles is likely to be suppressed.
[0058] [Aqueous medium] In the present disclosure, an aqueous medium means a medium selected from the group consisting of water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent. The hydrophilic solvent in the present disclosure is not particularly limited as long as it is sufficiently miscible with water and does not cause phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol, tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO). Among aqueous media, water is preferably used due to its high polarity. When using a mixture of water and a hydrophilic solvent, it is important that the polarity of the entire mixture is not too low from the viewpoint of forming polymerizable monomer droplets. In this case, for example, the mixture ratio (mass ratio) of water to hydrophilic solvent may be water:hydrophilic solvent=99:1 to 50:50.
[0059] In the mixed solution preparation step, the mixed solution may be obtained by simply mixing the above-mentioned materials and other materials as necessary and appropriately stirring or the like. However, in terms of making the shell more uniform, it is preferable to prepare a mixed solution by separately preparing in advance an oil phase containing a polymerizable monomer for the shell, a polar resin, and a hydrocarbon-based solvent, and an aqueous phase containing a dispersant and an aqueous medium, and mixing these to prepare the mixed solution. In the mixed liquid obtained in this step, the oil phase containing the above-mentioned shell polymerizable monomer, polar resin, oil-soluble polymerization initiator, and lipophilic materials such as a hydrocarbon solvent is dispersed with particle sizes of about several mm in the aqueous phase containing a dispersant and an aqueous medium, etc. The dispersion state of these materials in the mixed liquid can be observed with the naked eye depending on the type of material.
[0060] (B) Suspension process This step is a step of preparing a suspension in which polymerizable monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the above-mentioned mixed liquid. The suspension method for forming the polymerizable monomer droplets is not particularly limited, but may be carried out using a device capable of strong stirring, such as an in-line emulsifying disperser (manufactured by Pacific Machinery Works, product name: Milder) or a high-speed emulsifying disperser (manufactured by Primix Corporation, product name: TK Homomixer MARK II type). In the suspension prepared in the suspending step, polymerizable monomer droplets containing a hydrocarbon solvent are uniformly dispersed in an aqueous medium. The polymerizable monomer droplets are droplets with a diameter of about 3.0 μm to 30.0 μm, and are difficult to observe with the naked eye, but can be observed with a known observation device such as an optical microscope. In the suspension process, phase separation occurs in the polymerizable monomer droplets, and the hydrocarbon solvent with low polarity tends to collect inside the polymerizable monomer droplets. As a result, the obtained polymerizable monomer droplets have the hydrocarbon solvent distributed inside and materials other than the hydrocarbon solvent distributed around the periphery.
[0061] In the suspension process, the polymerizable monomer droplets are formed in advance, and then the oil-soluble polymerization initiator generates polymerization initiation radicals in the polymerizable monomer droplets. Therefore, precursor particles having a desired particle size can be produced without excessive growth of the polymerizable monomer droplets. In addition, in suspension polymerization, there is no opportunity for the oil-soluble polymerization initiator to come into contact with the polymerizable monomer dispersed in the aqueous medium, and therefore, by using the oil-soluble polymerization initiator, it is possible to suppress the generation of excess polymer particles such as dense solid particles having a relatively small particle size in addition to the intended resin particles having hollow portions.
[0062] (C) Polymerization process This step is a step of preparing a precursor composition containing precursor particles having hollow portions and encapsulating a hydrocarbon solvent in the hollow portions by subjecting the above-mentioned suspension to a polymerization reaction. In the polymerization process, the polymerizable monomer in the polymerizable monomer droplets is polymerized while the polymerizable monomer droplets still contain the hydrocarbon-based solvent, thereby forming precursor particles having a shell containing a resin, which is a polymerized product of the polymerizable monomer, and a hollow portion filled with the hydrocarbon-based solvent. In the manufacturing method of the present disclosure, in the polymerization step, the polymerizable monomer droplets are subjected to a polymerization reaction while encapsulating a hydrocarbon-based solvent, so that the polymerization reaction proceeds easily while maintaining the shape, and the size and porosity of the precursor particles are easily adjusted. In addition, when the polymerizable monomer for the shell is used in combination with a hydrocarbon-based solvent, the polarity of the hydrocarbon-based solvent is low relative to the shell of the precursor particle, and the hydrocarbon-based solvent is not easily compatible with the shell, so that phase separation occurs sufficiently and the hollow portion is likely to be only one. In addition, the size and porosity of the precursor particles can be easily adjusted by adjusting the amount of the hydrocarbon-based solvent, the amount of the polar resin, the type of dispersant, etc.
[0063] The polymerization method in the polymerization step is not particularly limited, and for example, a batch method, a semi-continuous method, a continuous method, etc. can be used. The polymerization temperature is preferably 40° C. or more and 80° C. or less, more preferably 50° C. or more and 70° C. or less. The polymerization reaction time is preferably 1 hour or more and 20 hours or less, more preferably 2 hours or more and 15 hours or less.
[0064] (D) Solvent removal process This step is a step of removing the hydrocarbon solvent contained in the precursor particles. The solvent removal step may be performed without separating the precursor particles from the aqueous medium in the precursor composition obtained by the polymerization step, or may be performed after the solid-liquid separation step of separating the precursor particles from the precursor composition. In the solid-liquid separation step, the method of separating the precursor particles from the precursor composition is not particularly limited as long as it is a method of separating a solid content containing the precursor particles and a liquid content containing the aqueous medium without removing the hydrocarbon solvent contained in the precursor particles, and a known method can be used. Examples of the solid-liquid separation method include a centrifugation method, a filtration method, and a static separation method, and among these, a centrifugation method or a filtration method may be used, and a centrifugation method may be adopted from the viewpoint of ease of operation. In addition, after the solid-liquid separation, preliminary drying may be performed before removing the hydrocarbon solvent in the precursor particles in air. The preliminary drying is performed, for example, by drying the solid content obtained after the solid-liquid separation with a drying device such as a dryer or a drying tool such as a hand dryer. do. Here, "in the air" refers to an environment in which no liquid exists outside the precursor particles, and an environment in which only a very small amount of liquid exists outside the precursor particles, to an extent that does not affect the removal of the hydrocarbon solvent. "In the air" can also be expressed as a state in which the precursor particles are separated from a slurry, or a state in which the precursor particles exist in a dry powder.
[0065] The method for removing the hydrocarbon solvent from the precursor particles in the air is not particularly limited, and any known method can be used, such as reduced pressure drying, heat drying, air flow drying, or a combination of these methods. In particular, when the heat drying method is used, the heating temperature must be equal to or higher than the boiling point of the hydrocarbon solvent and equal to or lower than the maximum temperature at which the shell structure of the resulting hollow particles does not collapse. Therefore, depending on the composition of the shell and the type of the hydrocarbon solvent, the heating temperature may be, for example, 40° C. or higher and 200° C. or lower. By the drying operation in air, the hydrocarbon solvent inside the precursor particles is replaced by the external gas, resulting in hollow particles whose hollow portions are filled with gas.
[0066] The drying atmosphere is not particularly limited and can be appropriately selected depending on the application of the hollow particles. Examples of the drying atmosphere include air, oxygen, nitrogen, argon, etc. Heat drying under vacuum conditions may be used. When the hydrocarbon solvent in the precursor particles is removed by drying under vacuum conditions, hollow particles with a temporary vacuum inside are obtained. In addition, hollow particles with a temporary vacuum inside can also be obtained by filling the inside of the hollow particles with a gas once and then drying under reduced pressure.
[0067] In addition to the steps described above, the method for producing hollow particles according to the present disclosure may further include other steps, such as the following (E) washing step and the following (F) hollow portion re-substitution step.
[0068] (E) Washing process This step is a step of adding an acid or alkali to wash the precursor composition containing the precursor particles before the solvent removal step in order to remove the dispersant remaining in the precursor composition containing the precursor particles. When the dispersant used is an inorganic compound soluble in acid, it is preferable to add an acid to the precursor composition containing the precursor particles to wash, while when the dispersant used is an inorganic compound soluble in alkali, it is preferable to add an alkali to the precursor composition containing the precursor particles to wash. Furthermore, when an inorganic compound soluble in acid is used as the dispersant, it is preferable to add an acid to the aqueous medium dispersion of the precursor composition containing the precursor particles to adjust the pH to preferably 6.5 or less, more preferably 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, etc., and organic acids such as formic acid, acetic acid, etc. can be used, but sulfuric acid is particularly preferable because of its high efficiency in removing the dispersant and its small burden on the production equipment.
[0069] (F) Re-replacement process of hollow part This step is a step of replacing the gas inside the hollow particles with another gas or solvent after the solvent removal step. By performing the hollow part re-substitution step, it is possible to change the environment inside the hollow particles, selectively confine molecules inside the hollow particles, or modify the chemical structure inside the hollow particles according to the application.
[0070] In one embodiment of the method for producing hollow particles of the present disclosure, two or more of the above steps may be performed simultaneously as one step, or the order of the steps may be changed, as far as technically possible. For example, the preparation of the mixture and the suspension may be performed simultaneously in one step, such as by adding the materials for preparing the mixture and suspending them at the same time.
[0071] II. Resin Composition The resin composition of the present disclosure is characterized by containing the hollow particles of the present disclosure and a resin. The resin composition of the present disclosure is usually obtained by kneading the hollow particles of the present disclosure, a resin, and additives added as necessary, and may be, for example, pellets. In the resin composition of the present disclosure, the hollow particles of the present disclosure are not easily crushed during kneading and molding after kneading, so that the hollow particles have the effect of reducing weight, etc. In addition, in the resin composition of the present disclosure, the content of volatile compounds in the hollow particles contained is reduced, so that foaming and ignition caused by the volatile compounds in the hollow particles are suppressed during kneading and molding after kneading.
[0072] The resin used in the resin composition of the present disclosure is not particularly limited, but is preferably a thermoplastic resin or a thermosetting resin. The thermoplastic resin may be any known one, and is not particularly limited. Examples of the thermoplastic resin include polyolefins such as polypropylene and polyethylene; polyamides such as PA6, PA66, and PA12; polyimide, polyamideimide, polyvinyl chloride, polystyrene, poly(meth)acrylate, polycarbonate, polyvinylidene fluoride, acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-styrene copolymer (AS), polyphenylene ether, polyphenylene sulfide, polyphenylene oxide, polyester, polytetrafluoroethylene, cyanate resin, and thermoplastic elastomer. These thermoplastic resins can be used alone or in combination of two or more kinds. The thermosetting resin may be any known resin, and may include, but is not limited to, phenol-based resins, melamine-based resins, urea-based resins, unsaturated polyester-based resins, epoxy-based resins, polyurethane-based resins, silicone-based resins, and alkyd-based resins. These thermosetting resins can be used alone or in combination of two or more kinds. In addition, when the resin composition of the present disclosure contains a thermosetting resin, it may further contain, as necessary, a crosslinking agent for crosslinking the thermosetting resin by heat, and a solvent for dissolving or dispersing each component, etc. As the crosslinking agent, a known one can be used, and is appropriately selected depending on the type of thermosetting resin.
[0073] The content of the resin in the resin composition of the present disclosure (100% by mass) is not particularly limited, but is usually 70% by mass or more and 99% by mass or less. When the content of the resin is equal to or more than the lower limit, the resin composition has excellent moldability when molded into a molded article, and the obtained molded article has excellent mechanical strength, while when the content of the resin is equal to or less than the upper limit, the hollow particles of the present disclosure can be sufficiently contained, thereby making it possible to reduce the weight of the resin composition. The content of the hollow particles of the present disclosure in the total mass (100 mass%) of the resin composition of the present disclosure is not particularly limited, but is usually 1 mass% or more and 30 mass% or less. When the content of the hollow particles is equal to or more than the lower limit, the resin composition can be sufficiently lightened, while when the content of the hollow particles is equal to or less than the upper limit, the resin can be sufficiently contained, thereby improving moldability.
[0074] In addition to the hollow particles and resin of the present disclosure, the resin composition of the present disclosure may further contain additives such as ultraviolet absorbers, colorants, heat stabilizers, and fillers, as necessary, within a range that does not impair the effects of the present disclosure. In addition, the resin composition of the present disclosure may further contain organic or inorganic fibers such as carbon fibers, glass fibers, aramid fibers, and polyethylene fibers.
[0075] The resin composition of the present disclosure can be obtained, for example, by mixing the hollow particles of the present disclosure, the resin, and additives that are further added as necessary, followed by kneading. The kneading can be carried out by a known method, and is not particularly limited. For example, the kneading can be carried out using a kneading device such as a single-screw kneader or a twin-screw kneader. When the resin in the resin composition of the present disclosure is a thermoplastic resin, the kneading is performed by heating the resin composition to melt the thermoplastic resin. The temperature during the melt kneading is not particularly limited as long as it is a temperature at which the thermoplastic resin used can be melted, but it is preferable that the temperature is 250°C or less in order to suppress the collapse of the hollow particles. When the resin composition of the present disclosure is made into pellets, the resin in the resin composition is usually a thermoplastic resin, and after the melt kneading, the resin composition can be molded into pellets by a known molding method such as extrusion molding or injection molding. On the other hand, when the resin in the resin composition of the present disclosure is a thermosetting resin, the kneading may be carried out in a temperature environment below the curing temperature of the thermosetting resin, and is not particularly limited, but is usually carried out in a temperature environment of 180°C or higher and 240°C or lower.
[0076] III. Molded object The molded article of the present disclosure is an article molded from the resin composition of the present disclosure. The molded article of the present disclosure contains the hollow particles of the present disclosure which are suppressed from being crushed, and thus effectively exhibits the effects of the hollow particles, such as weight reduction.
[0077] The molded article of the present disclosure can be obtained by molding the above-described resin composition of the present disclosure. When the resin composition of the present disclosure contains the thermoplastic resin, the molded article of the present disclosure can be obtained, for example, by melt-kneading the resin composition of the present disclosure and then molding it into a desired shape by a known molding method such as extrusion molding, injection molding, press molding, etc. The melt-kneading method used to obtain the molded article of the present disclosure may be the same as the melt-kneading method used to obtain the resin composition of the present disclosure described above.
[0078] On the other hand, when the resin composition of the present disclosure contains the thermosetting resin, the molded body of the present disclosure can be obtained, for example, by applying the resin composition of the present disclosure to a support, drying it if necessary, and then curing it by heating. Examples of materials for the support include resins such as polyethylene terephthalate and polyethylene naphthalate; and metals such as copper, aluminum, nickel, chromium, gold, and silver. The resin composition containing the thermosetting resin can be applied by a known method, such as dip coating, roll coating, curtain coating, die coating, slit coating, and gravure coating. When the resin composition of the present disclosure contains a solvent, it is preferable to dry the resin composition of the present disclosure after the coating. The drying temperature is preferably a temperature at which the resin composition does not harden, from the viewpoint of removing the solvent while leaving the resin composition in an uncured or semi-cured state, and is usually 20°C or higher and 200°C or lower, preferably 30°C or higher and 150°C or lower. The drying time is usually 30 seconds or higher and 1 hour or lower, preferably 1 minute or higher and 30 minutes or lower. The heating temperature for curing the resin composition of the present disclosure is appropriately adjusted according to the type of thermosetting resin, and is not particularly limited, but is usually 30°C to 400°C, preferably 70°C to 300°C, and more preferably 100°C to 200°C. The curing time is 5 minutes to 5 hours, preferably 30 minutes to 3 hours. The heating method is not particularly limited, and may be performed using, for example, an electric oven.
[0079] The shape of the molded body of the present disclosure is not particularly limited, and can be any shape that can be molded using the resin composition of the present disclosure, for example, it may be a sheet, film, or plate. When the molded body of the present disclosure contains fibers, the fibers in the molded body may be in the form of a nonwoven fabric. When the molded body of the present disclosure contains fibers, it may be a molded body of a resin composition in which hollow particles of the present disclosure are added to a fiber-reinforced plastic containing the resin and fibers as described above. Examples of applications of the molded article of the present disclosure include light reflecting materials, heat insulating materials, sound insulating materials, and low dielectric materials used in various fields such as automobiles, electrical appliances, electronics, construction, aviation, and space, as well as food containers. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Note that parts and % are by weight unless otherwise specified. In the following, the number average molecular weight was measured as a polystyrene-equivalent molecular weight by gel permeation chromatography (GPC) using tetrahydrofuran as a carrier at a flow rate of 0.35 ml / min. The apparatus used was a Tosoh HLC8220, the column was a combination of three Showa Denko Shodex (registered trademark) KF-404HQ columns (column temperature 40°C), and the detectors were a differential refractometer and an ultraviolet detector. The molecular weight was calibrated at 12 points using standard polystyrene (5 to 3 million) manufactured by Polymer Laboratory.
[0081] [Production Example 1: Production of Polar Resin A (MMA / AA / EA Copolymer)] 200 parts of toluene were added to the reaction vessel, and the inside of the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 96.2 parts of methyl methacrylate (MMA), 0.3 parts of acrylic acid (AA), 3.5 parts of ethyl acrylate (EA), and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin A (MMA / AA / EA copolymer). Of the total mass of repeating units constituting the obtained polar resin A (MMA / AA / EA copolymer), 100%, the proportion of repeating units derived from MMA was 96.2%, the proportion of repeating units derived from AA was 0.3%, and the proportion of repeating units derived from EA was 3.5%. The number average molecular weight of the resulting polar resin A (MMA / AA / EA copolymer) was 10,000.
[0082] [Production Example 2: Production of Polar Resin B (MMA / HEMA / EA Copolymer)] 200 parts of toluene were added to the reaction vessel, and the inside of the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 95.0 parts of methyl methacrylate (MMA), 3.0 parts of 2-hydroxyethyl methacrylate (HEMA), 2.0 parts of ethyl acrylate (EA), and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin B (MMA / HEMA / EA copolymer). Of the total mass of repeating units constituting the obtained polar resin B (MMA / HEMA / EA copolymer), 100%, the proportion of repeating units derived from MMA was 95.0%, the proportion of repeating units derived from HEMA was 3.0%, and the proportion of repeating units derived from EA was 2.0%. The number average molecular weight of the resulting polar resin B (MMA / HEMA / EA copolymer) was 10,000.
[0083] [Polar resin C (PMMA)] 200 parts of toluene were added to the reaction vessel, and the atmosphere in the reaction vessel was thoroughly replaced with nitrogen while stirring the toluene, and then the temperature was raised to 90°C, and then a mixed solution of 100 parts of methyl methacrylate (MMA) and 2.8 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name: Perbutyl O) was dropped into the reaction vessel over 2 hours. The mixture was further kept under toluene reflux for 10 hours to complete polymerization, and then the solvent was distilled off under reduced pressure to obtain polar resin C (PMMA), which was a homopolymer of MMA. The number average molecular weight of the obtained polar resin C (PMMA) was 6,000.
[0084] [Example 1] (1) Mixed liquid preparation process First, the following materials were mixed to prepare an oil phase. Ethylene glycol dimethacrylate 100 parts Polar resin A (MMA / AA / EA copolymer) 2 parts 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65) 3 parts Cyclohexane 187 parts Meanwhile, in a stirring tank at room temperature, an aqueous solution of 5.5 parts of sodium hydroxide (alkali metal hydroxide) in 55 parts of ion-exchanged water was gradually added under stirring to an aqueous solution of 7.8 parts of magnesium chloride (water-soluble polyvalent metal salt) in 225 parts of ion-exchanged water to prepare a magnesium hydroxide colloid (poorly water-soluble metal hydroxide colloid) dispersion, which was used as the aqueous phase. A mixture was prepared by mixing the water phase and the oil phase.
[0085] (2) Suspension process The mixture obtained in the above mixture preparation step was stirred and suspended for 1 minute using a disperser (manufactured by Primix Corporation, product name: Homomixer) at a rotation speed of 4,000 rpm to prepare a suspension in which monomer droplets encapsulating cyclohexane were dispersed in water.
[0086] (3) Polymerization process The suspension obtained in the above suspension step was stirred for 4 hours under a nitrogen atmosphere at a temperature of 65° C. to carry out a polymerization reaction. Through this polymerization reaction, a precursor composition containing precursor particles encapsulating cyclohexane was prepared.
[0087] (4) Washing process and solid-liquid separation process The precursor composition obtained in the polymerization step was washed with dilute sulfuric acid at 25°C for 10 minutes to adjust the pH to 5.5 or less. Next, after separating the water by filtration, 200 parts of ion-exchanged water was added to reslurry the mixture, and the water washing treatment (washing, filtration, dehydration) was repeated several times at 25°C, followed by filtration and separation to obtain a solid content. The obtained solid content was dried in a dryer at a temperature of 40°C to obtain precursor particles containing cyclohexane.
[0088] (5) Solvent removal process The precursor particles obtained in the solid-liquid separation step were heat-treated in a vacuum dryer at 200° C. for 6 hours under vacuum conditions, then the pressure was returned to normal with nitrogen and cooled to room temperature to obtain hollow particles of Example 1. From the results of observation with a scanning electron microscope and the porosity value, it was confirmed that these particles were spherical and had hollow portions.
[0089] [Examples 2 to 10, Comparative Examples 1 to 7] The hollow particles of Examples 2 to 10 and Comparative Examples 1 to 7 were obtained in the same manner as in Example 1, except that the composition of the oil phase prepared in the above "(1) Mixture preparation step" was as shown in Table 1.
[0090] [evaluation] The hollow particles obtained in Examples 1 to 10 and Comparative Examples 1 to 7 were subjected to the following measurements and evaluations.
[0091] 1. Volume average diameter of hollow particles The particle size of the hollow particles was measured using a laser diffraction particle size distribution measuring instrument (manufactured by Shimadzu Corporation, product name: SALD-2000), and the volume average was calculated to obtain the volume average particle size.
[0092] 2. Density and porosity of hollow particles 2-1. Measurement of apparent density of hollow particles First, the capacity is 100 cm 3 About 30 cm 3 The hollow particles were filled into the measuring flask, and the mass of the filled hollow particles was precisely weighed. Next, the measuring flask filled with the hollow particles was precisely filled with isopropanol up to the mark, while being careful not to introduce air bubbles. The mass of isopropanol added to the measuring flask was precisely weighed, and the apparent density D of the hollow particles was calculated based on the following formula (I). 1 (g / cm 3 ) was calculated. Formula (I) Apparent density D 1 = [Mass of hollow particles] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at measurement temperature])
[0093] 2-2. Measurement of true density of hollow particles After crushing the hollow particles in advance, 3 Approximately 10 g of crushed pieces of hollow particles were filled into a measuring flask, and the mass of the filled crushed pieces was accurately weighed. Then, in the same manner as in the measurement of the apparent density, isopropanol is added to the measuring flask, the mass of isopropanol is accurately weighed, and the true density D of the hollow particles is calculated based on the following formula (II). 0 (g / cm 3 ) was calculated. Formula (II) true density D 0 = [Mass of crushed hollow particle pieces] / (100-[Mass of isopropanol]÷[Specific gravity of isopropanol at the measurement temperature])
[0094] 2-3. Calculation of void ratio Apparent density D 1 The true density D 0 The result was divided by the square root of the particle diameter and multiplied by 100, and the result was subtracted from 100 to obtain the porosity (%) of the hollow particle.
[0095] 3.Shell thickness of hollow particles The inner diameter r of the hollow particles was calculated from the volume average particle diameter R and porosity of the hollow particles according to the following formula (1), and the shell thickness of the hollow particles was calculated from the inner diameter r and the volume average particle diameter R according to the following formula (2). 4 / 3π×(R / 2) 3 ×Porosity=4 / 3π×(r / 2) 3 Formula (1) Shell thickness = (Rr) / 2 Equation (2)
[0096] 4. Amount of volatile compounds in hollow particles The content of volatile compounds in the hollow particles was measured by the following method. Approximately 100 mg of hollow particles were placed in a 30 mL screw-top glass bottle and weighed accurately. Then, approximately 10 g of tetrahydrofuran (THF) was placed in the bottle and weighed accurately. The mixture in the glass bottle was stirred with a stirrer for 1 hour to extract volatile compounds such as hydrocarbon solvents contained in the hollow particles (cyclohexane (boiling point 80.74°C, molecular weight 84.16), ethylene glycol dimethacrylate (boiling point 235°C, molecular weight 198.22), methyl methacrylate (boiling point 101°C, molecular weight 100.12), etc.). The stirring was stopped, and the resin components of the hollow particles that were insoluble in THF were precipitated. A filter (Advantec, product name: Membrane Filter 25JP020AN) was attached to the syringe to filter the precipitate and obtain a sample liquid. The sample liquid was injected into a gas chromatograph (GC) for analysis. The amount of volatile compounds (mass%) contained in the hollow particles per unit mass was calculated from the GC peak area and a calibration curve prepared in advance. The detailed analysis conditions are as follows: (Analysis conditions) Equipment: GC-2010 (Shimadzu Corporation) Column: DB-5 (Agilent Technologies, Inc.) Film thickness 0.25μm, inner diameter 0.25mm, length 30m Detector: FID Carrier gas: Nitrogen (linear velocity: 28.8 cm / sec) Inlet temperature: 200℃ Detector temperature: 250℃ Oven temperature: Increase from 40°C to 230°C at a rate of 10°C / min, and hold at 230°C for 2 minutes. Sampling volume: 2μL
[0097] [result] Table 1 shows the types and amounts of materials used in Experimental Examples 1 to 10 and Comparative Examples 1 to 7, as well as the evaluation results for the obtained hollow particles.
[0098] [Table 1]
[0099] In addition, 100 hollow particles each obtained in Examples 1 to 10 were observed with an SEM, and the presence or absence of interconnected holes with a diameter of about 10 nm to 500 nm and crack-like shell defects with a length of 1 μm or more was confirmed in each particle. As a result, for the hollow particles obtained in each Example, the number of hollow particles having the interconnected holes or shell defects was 5 or less out of 100. This confirmed that hollow particles having substantially no interconnected holes or shell defects were obtained in Examples 1 to 10.
[0100] [Example 11] Polypropylene as a thermoplastic resin (manufactured by Mitsubishi Chemical, product name: MA1B, specific gravity 0.90 g / cm 3 90 parts of the cellulose acylate sintered body) and 10 parts of the hollow particles obtained in Example 1 were mixed in a blender. The mixture was then kneaded under the following kneading conditions using a twin-screw kneader (manufactured by Toshiba Machine Co., Ltd., product name: TEM-35B), extruded, and pelletized to obtain pellets of a resin composition. <Mixing conditions> Screw diameter 37mm, L / D=32 Screw rotation speed: 250 rpm Resin temperature 190℃ Feed rate 20kg / hour The resulting resin composition pellets were dried by heating at 80°C for 6 hours, and then molded using an injection molding machine under the following molding conditions to obtain a molded product with dimensions of 80 mm x 10 mm x thickness of 4 mm. The specific gravity of the resulting molded product was measured by the underwater displacement method in accordance with JIS K 7112. <Molding conditions> Cylinder temperature: 230℃ Mold temperature: 40℃ Injection pressure: 70MPa
[0101] [Examples 12 to 22, Comparative Examples 8 to 10] In Example 11, instead of the hollow particles obtained in Example 1, hollow particles obtained in the Examples or Comparative Examples shown in Table 2 were used, and in Examples 21 and 22, PA-6 (manufactured by Unitika Ltd., product name: A1020BRL, specific gravity 1.13 g / cm) was used as the thermoplastic resin instead of polypropylene. 3The resin compositions and molded articles of Examples 12 to 22 and Comparative Examples 8 to 10 were obtained in the same manner as in Example 11, except that 2-methyl-2-propanediol was used instead of 2-methyl-2-propanediol.
[0102] [Comparative Example 11] A resin composition and a molded body of Comparative Example 11 were obtained in the same manner as in Example 11, except that the amount of polypropylene added was changed to 80 parts, and 20 parts of glass balloons (manufactured by 3M, product name: Glass Bubbles iM30K) were used instead of 10 parts of the hollow particles obtained in Example 1.
[0103] The weight reduction rate and specific gravity increase rate of the molded bodies obtained in Examples 11 to 22 and Comparative Examples 8 to 11 were calculated by the following formulas. Weight reduction rate (%) = 100 x (1 - specific gravity of molded body / specific gravity of thermoplastic resin alone) Specific gravity increase rate (%) = 100 × (specific gravity of molded body / theoretical specific gravity of resin composition - 1) The theoretical density of the resin composition is calculated by the weight ratio of the thermoplastic resin to the hollow particles and their respective specific gravities (apparent density D 1 ) was calculated. The specific gravity increase rate is also an index for evaluating the degree to which hollow particles are crushed during kneading and molding of the resin composition. If the hollow particles in the resin composition are not crushed at all during kneading and molding, the specific gravity of the resulting molded product will be the same as the theoretical specific gravity of the resin composition, and the specific gravity increase rate will be 0%. Therefore, the smaller the specific gravity increase rate, the more difficult it is for hollow particles to be crushed during kneading and molding of the resin composition.
[0104] [Table 2]
[0105] [Consideration] The hollow particles of Experimental Examples 1 to 10 and Comparative Examples 1 to 7 will be discussed below with reference to Tables 1 and 2. The hollow particles of Comparative Example 1 had a crosslinkable monomer ratio of 60% by mass and a non-crosslinkable monomer ratio of 40% by mass in 100% by mass of the shell polymerizable monomer used, and thus the ratio of the crosslinkable monomer was low and the ratio of the non-crosslinkable monomer was high, and therefore the particles were easily crushed during kneading with the thermoplastic resin and during molding after kneading. Therefore, as shown in Comparative Example 8, the molded product to which the hollow particles of Comparative Example 1 were added had a low weight reduction rate and a high specific gravity increase rate. The hollow particles of Comparative Example 2 had a low porosity of 40% and a shell thickness of more than 0.9 μm, and therefore contained a large amount of volatile compounds remaining within the particles. The hollow particles of Comparative Examples 3, 5, and 7 did not contain a polar resin and had a shell thickness exceeding 0.9 μm, so that a large amount of volatile compounds remained within the particles. The hollow particles of Comparative Example 4 had a high porosity of 92% and a shell thickness of less than 0.2 μm, and therefore were easily crushed during kneading with the thermoplastic resin and during molding after kneading. Therefore, as shown in Comparative Example 9, the molded product to which the hollow particles of Comparative Example 4 were added had a low weight reduction rate and a high specific gravity increase rate. The hollow particles of Comparative Example 6 had a shell thickness of less than 0.2 μm, and therefore were easily crushed during kneading with the thermoplastic resin and during molding after kneading. Therefore, as shown in Comparative Example 10, the molded product to which the hollow particles of Comparative Example 6 were added had a low weight reduction rate and a high specific gravity increase rate. Moreover, the molded product of Comparative Example 11, which used glass balloons instead of the hollow particles of the present disclosure, had a low weight reduction rate and a high specific gravity increase rate, which is believed to be because the glass balloons could not withstand the load during kneading and molding after kneading and broke.
[0106] On the other hand, the hollow particles of Examples 1 to 10 have a porosity in the range of 50% to 90%, a moderately high porosity, a shell thickness of 0.2 μm to 0.9 μm, and the shell contains a polymer derived from a shell polymerizable monomer consisting of 70% to 100% by mass of a crosslinkable monomer and 0% to 30% by mass of a non-crosslinkable monomer, and a polar resin, so that the content of volatile compounds in the particles is low, and the particles are not easily crushed during kneading with a thermoplastic resin and during molding after kneading, and as shown in Examples 11 to 22, the molded bodies to which the hollow particles of Examples 1 to 10 are added have a high weight reduction rate and a low specific gravity increase rate. This makes it clear that the hollow particles of Examples 1 to 10 are useful as weight-reducing materials.
Claims
1. A hollow particle having a shell and a hollow portion surrounded by the shell, the hollow particle having a porosity of 50% or more and 90% or less, the shell has a thickness of 0.2 μm or more and 0.9 μm or less, and contains a polymer derived from a polymerizable monomer for the shell (wherein the total mass of the polymerizable monomer for the shell is 100 mass%) consisting of 70 mass% or more and 100 mass% or less of a crosslinkable monomer and 0 mass% or more and 30 mass% or less of a non-crosslinkable monomer, and a polar resin which is an acrylic resin; the crosslinkable monomer contained in the shell polymerizable monomer is at least one selected from the group consisting of ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate, the non-crosslinkable monomer contained in the shell polymerizable monomer is a (meth)acrylic monovinyl monomer, The hollow particles, wherein the polar resin is an acrylic resin, which is a polymer derived from a polymerizable monomer for a polar resin containing 50.0% by mass or more of methyl methacrylate (wherein the total mass of the polymerizable monomer for a polar resin is taken as 100% by mass).
2. The hollow particle described in claim 1, wherein the non-crosslinkable monomer contained in the shell polymerizable monomer is at least one type of (meth)acrylic monovinyl monomer selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate.
3. 3. The hollow particle according to claim 1, wherein the content of the polar resin is 0.1 parts by mass or more and 10.0 parts by mass or less based on 100 parts by mass of the polymerizable monomer for the shell.
4. 4. The hollow particle according to claim 1, wherein the acrylic resin as the polar resin is a copolymer derived from a polymerizable monomer for a polar resin, the polymerizable monomer comprising 50.0% by mass or more and 99.9% by mass or less of methyl methacrylate and 0.1% by mass or more and 5.0% by mass or less of a polar group-containing monomer containing at least one polar group selected from a carboxyl group, a hydroxyl group, a sulfonic acid group, an amino group, a polyoxyethylene group, and an epoxy group (wherein the total mass of the polymerizable monomer for the polar resin is taken as 100% by mass).
5. A resin composition comprising the hollow particles according to claim 1 and a resin.
6. A molded article of the resin composition according to claim 5.
Citation Information
Patent Citations
Hollow polymer fine particle and method for producing the same
JP2002080503A
Magnetic body holding particulate and manufacturing method therefor
JP2003015171A
Fine particle having opening and its manufacturing method
JP2005232426A
Magnetic particulate for use in magnetic heat-sensitive electronic paper
JP2006257414A
Hollow particle and manufacturing method therefor
JP2015229731A